Construction and practice of anorectal specialty nursing alliance platform (肛肠专科护理联盟平台的建设与实践) - SUI Tingting (隋婷婷); WEI Guojun (魏国君); GUO Yufan (郭雨凡); WEI Ying (魏莹); LIU Jiawei (刘佳伟); WANG Yanzhi (王艳芝) (中西医结合护理)
This paper puts forward some suggestions on the construction of anorectal specialty nursing alliance platform from the aspects of work planning, organizational structure, post responsibilities and work objectives at all levels. The aim of this paper is to promote the sharing of specialized nursing standards and nursing norms within the nursing alliance, jointly improve the quality management of anorectal specialized nursing, improve the clinical research and academic level of specialized nursing, further improve the training of specialized nursing talents, jointly win the social benefits of specialized nursing, establish regional anorectal specialized nursing alliance, and promote the vigorous development of anorectal specialized medical association. (本文总结了肛肠专科护理联盟平台建设与实践的相关经验, 包括工作规划、组织构架、各级岗位职责及工作目标等内容, 为推动护理联盟内专科护理标准及护理规范的共享, 提高肛肠专科护理质量管理, 提升专科护理临床研究与学术水平, 完善专科护理人才培养, 实现专科护理的社会效益提供参考和借鉴。)